Partial characterization, quantification and activity of pancreatic lipase in the gastrointestinal tract of Totoaba macdonaldi - González-Félix, Mayra L.; Santana-Bejarano, Edna B.; Perez-Velazquez, Martin; Villalba-Villalba, Ana G. (Archives of Biological Sciences, 2018)
Paper description: Pancreatic lipase is one of the main enzymes in higher vertebrates. It participates in the digestion of dietary lipid, one of the crucial macronutrients. Knowledge of the type of lipase present in a particular fish species and its functional characteristics can contribute to the understand of its digestive physiology. This type of knowledge has not been advanced significantly for cultured fish species of commercial importance. Totoaba macdonaldi has great potential as a candidate species for aquaculture. Studying the enzymatic action and potential of its pancreatic lipase will contributes to a better understanding of lipid catabolism which could help improve formulations of balanced feeds. Abstract: Lipids are one of the main macronutrients that constitute balanced feeds used in aquaculture. Adequate utilization of dietary lipid is influenced by the activity of pancreatic lipase, one of the enzymes that promotes digestion of dietary lipids in the gastrointestinal tract of fish. The culture of Totoaba macdonaldi is quite recent; its nutritional requirements have been partially established. Knowing the characteristics of pancreatic lipase for this species could help optimize the dietary lipids included in balanced feeds for its culture. Therefore, the aim of this work is to partially characterize and evaluate the enzymatic activity of pancreatic lipase for T. macdonaldi. Biological indices showed that experimental organisms had a good nutritional status. Pancreatic lipase molecular weight was determined by native sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and its activity was evaluated in crude enzymatic extracts from different gastrointestinal tract regions. The molecular weight of lipase was estimated to be 70.4 kDa; the highest lipolytic activity was observed at 45°C and at a pH optimum of 8.0 in the anterior intestine and pyloric caeca, where the concentration and activity of the enzyme was significantly higher (P=0.004) compared to the distal parts of the intestine. Biochemical characteristics observed for the pancreatic lipase of T. macdonaldi are quite similar to other lipases of fish cultured worldwide; results provided in this study will help understand the role this lipolytic enzyme plays in the digestive process of this species. https://doi.org/10.2298/ABS180202009G Received: February 2, 2018; Revised: March 16, 2018; Accepted: March 16, 2018; Published online: March 21, 2018 How to cite this article: González-Félix ML, Santana-Bejarano EB, Perez-Velazquez M, Villalba-Villalba AG. Partial characterization, quantification and activity of pancreatic lipase in the gastrointestinal tract of Totoaba Macdonaldi. Arch Biol Sci. 2018;70(3):…